2005
DOI: 10.2320/matertrans.46.1295
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Compound Formation and Growth Kinetics in Flip Chip Joints Using Sn–3.0Ag–0.5Cu Solder and Ni–P under Bump Metallurgy

Abstract: The interfacial microstructure of Sn-3.0Ag-0.5Cu solder with ENIG (electroless Ni/immersion Au) UBM was studied using scanning electron microscopy and transmission electron microscopy. (Cu,Ni) 6 Sn 5 intermetallic compound layer was formed at the interface between the solder and Ni-P under bump metallization upon reflow. However, after isothermal aging, some AuSn 4 but with a certain amount of Ni dissolved in it, i.e., (Au,Ni)Sn 4 , appeared above the (Cu,Ni) 6 Sn 5 layer. Two distinctive layers, P-rich and Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…14) Considering all these data, this ternary phase is believed to be Ni 3 SnP compound. It is noted that this layer was also found in the study about the interfacial reaction between the Sn-Ag-Cu/electroless Ni-P. 20) This means that the Ag element addition to the Sn-Cu solder has not significant influence on the interfacial reactions between solder and Ni-P layer. Figure 4 shows the variations of the IMC layer thickness as a function of square root of aging time for different aging temperatures.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…14) Considering all these data, this ternary phase is believed to be Ni 3 SnP compound. It is noted that this layer was also found in the study about the interfacial reaction between the Sn-Ag-Cu/electroless Ni-P. 20) This means that the Ag element addition to the Sn-Cu solder has not significant influence on the interfacial reactions between solder and Ni-P layer. Figure 4 shows the variations of the IMC layer thickness as a function of square root of aging time for different aging temperatures.…”
Section: Resultsmentioning
confidence: 75%
“…This was already shown in our previous study concerning the interfacial reaction of Sn-Ag-Cu/Ni-P combination. 20) Huang and Suganuma also reported that the P-rich layer was consisted of Ni 3 P and Ni in the Sn-3.5Ag and Ni-P UBM system with their selected area diffraction (SAD) pattern studies. 14) From our TEM-EDS analyses, the averaged composition of the layer is more close to that of mixture of the Ni 3 P and Ni than that of pure Ni 3 P compound.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a Ni-Sn-P phase formed between IMCs and Ni-P UBM causes IMCs to be spalled into the solder matrix, resulting in a reliability concern. [14][15][16][17][18][19][20][21][22] More recently, the detailed formation configuration for Ni x P y layers and Ni-Sn-P in the Sn-Ag-Cu/Ni-P UBM solder joint was intensively investigated with a newly developed field emission electron probe microanalyzer. 22 It is argued that the formation of Ni-Sn-P is significantly dependent on the phosphorous content of Ni-P UBM.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent European Union directives, RoHS (Restriction of the use of certain Hazardous Substances) and WEEE (Waste Electrical and Electronic Equipment), require new electrical and electronic equipment produced after July 1, 2006 to be Pb-free. 3,4) In response to these legislations, most major electronic manufacturers have stepped up their search for alternatives to the Sn-37Pb solder.…”
Section: Introductionmentioning
confidence: 99%